Influence of the Level of Education, Occupation, Experience, and Professional Training on the Income of Female Employees in Azerbaijan - Namazova, Natavan (Journal of Ecohumanism, 2025)
Various factors affect the income of female employees. The study examined the influence of factors such as education level, experience, occupation, and professional training on the income of female workers in Azerbaijan. To this end, 582 women employees working in the private sector in Azerbaijan were invited to participate in the survey, and the collected data were subjected to the ANOVA test. According to the results of one-way analysis of variance by occupation, there is no relationship between the occupation and earnings of working women. However, level of education, experience, and professional training have been found to impact the earnings of working women. Based on the results of the study, policies to improve women’s incomes in the country can be implemented.